Market Research and Innovation Strategy in a Duopoly - Lauga, Dominique Olié; Ofek, Elie (Marketing Science, 2009)
We model a duopoly in which ex ante identical firms must decide where to direct their innovation efforts. The firms face market uncertainty about consumers' preferences for innovation on two product attributes and technology uncertainty about the success of their research and development (R&D) investments. Firms can conduct costly market research before setting R&D strategy. We find that the value of market information to a firm depends on whether its rival is expected to obtain this information in equilibrium. Consequently, one firm may forgo market research even though its rival conducts such research and learns the true state of demand. We examine both vertical and horizontal demand structures. With vertical preferences, firms are a priori uncertain about which attribute all consumers will value more. In this case, a firm that conducts market research always attempts innovation on the attribute it discovers that consumers prefer and expends more on R&D than a rival that has not conducted market research. With horizontal preferences, distinct segments exist—each caring about innovation on only one attribute—and firms are a priori uncertain how many consumers each segment contains. In this case, a firm that conducts market research may follow a niche strategy and attempt innovation to serve the smaller segment to avoid intense price competition for the larger segment. A firm that conducts market research may therefore invest less in R&D and earn lower postlaunch profits than a rival that has forgone such research.